Adverse events following COVID-19 vaccination in South Korea between February 28 and August 21, 2021: A nationwide observational study. (May 2022) - Lee, Dong Seok; Kim, Ji Won; Lee, Kook Lae; Jung, Yong Jin; Kang, Hyoun Woo
Highlights: The incidence of adverse reactions after COVID-19 vaccinations was <1% in the study population. Adverse reactions varied in severity with age, sex, and dose order. Most adverse events occurred after the first dose and within 1 day of vaccination. The frequency of adverse reactions was higher in women than in men. Severe adverse reactions and mortality events increased with age. Abstract: Objectives: To investigate the clinical characteristics of adverse events (AEs) after COVID-19 vaccination in patients in South Korea. Design: Data from the Korean Disease Control and Prevention Agency on AEs from 4 COVID-19 vaccines, including AZD1222, BNT162b2, JNJ-78436735, and mRNA-1273, from February 26, 2021, to August 21, 2021, were assessed. The epidemiological characteristics, clinical symptoms, severity, complications, and mortality were descriptively analyzed. Results: Overall, 36.3 million individuals who completed the COVID-19 vaccination doses during the study period were included, and 153, 183 AEs were reported. Most AEs occurred after the first dose (80.6%) and within a day (63.2%) after vaccination. Of the AEs, 95.5% were nonsevere cases; however, 4.5% were severe. Most mild AEs showed a similar frequency across all age groups, but major severe AEs and mortality events increased with age. Conclusions: Although there were differences in the frequency of occurrence, various adverse reactions were confirmed in using all 4 COVID-19 vaccines, even with the BNT162b2 (Pfizer-BioNTech) vaccine. Caution is needed, and further research should be continuously conducted.